Establishing Social Reharmonization between the Balinese Hindu Diaspora and Sasak Moslem in Post-Conflict in Mataram - I Wayan Ardhi Wirawan (Pusat Kajian Bali Universitas Udayana, 2020)
This research aims to study the revitalization of quotidian ties as a medium of establishing social reharmonization between the Balinese Hindu diaspora and Sasak Moslem in Mataram city. This revitalization was carried out post-conflict between the two ethnic groups in a number of areas. This phenomenon is related to the representation of local wisdom as posessing noble values instilled by the ancestors of the two ethnic groups toward realizing mutualistic communication and interaction. This study was designed using an interpretative-descriptive approach in order to conduct an in-depth analysis of the research focus. This study found innovations relating to the implementation of quotidian ties, specifically through the revitalization of individual and collective consciousness based on quotidian ties, the strengthening of multicultural ties between the two ethnic communities, the valorization of local wisdom involving the participation of different ethnic groups, and the contestation of cultural capital in the implementation of adat and religious practices. Recommendations of this study are to build cultural awareness through attitudes that mutually recognize and accept differences.Keywords: revitalization, quotidian ties, Balinese Hindu, Sasak Moslem, social reharmonization